Capacity Building for Health Care Workers and Support Staff in Pediatric Emergency Triage Assessment and Treatment (ETAT) at Primary Health Care Level in Resource Limited Settings: Experiences from Malawi. Issue 2 (3rd April 2022) - Majamanda, Maureen Daisy; Joshua Gondwe, Mtisunge; O'Byrne, Thomasena; Makwero, Martha; Chalira, Alfred; Lufesi, Norman; Dube, Queen; Desmond, Nicola
ABSTRACT: Primary health care facilities offer an entry point to the health care system in Malawi. Challenges experienced by these facilities include limited resources (both material and human), poor or inadequate knowledge, skills and attitudes of health care workers in emergency management, and delay in referral from primary care level to other levels of care. These contribute to poor outcomes including children dying within the first 24 hours of hospital admission. Training of health care workers and support staff in Emergency Triage Assessment and Treatment (ETAT) at primary care levels can help improve care of children with acute and severe illnesses. Health care workers and support staff in the primary care settings were trained in pediatric ETAT. The training package for health care workers was adapted from the Ministry of Health ETAT training for district and tertiary health care. Content for support staff focused on non-technical responsibility for lifesaving in emergency situations. The primary health care facilities were provided with a minimum treatment package comprising emergency equipment, supplies and drugs. Supportive supervisory visits were conducted quarterly. The training manual for health care workers was adapted from the Ministry of Health package and the support staff training manual was developed from the adapted package. Eight hundred and seventy-seven participants were trained (336 health care workers and 541 support staff). Following the training, triaging of patients improved and patients were managed as emergency, priority or non-urgent. This reduced the number of referral cases and children were stabilized before referral. Capacity building of health care workers and support staff in pediatric ETAT and the provision of a basic health center package improved practice at the primary care level. The practice was sustained through institutional mentorship and pre-service and in-service training. The practice of triage and treatment including stabilization of children with dangerous signs at the primary health care facility improves emergency care of patients, reduces the burden of patients on referral hospitals and increases the number of successful referrals.